An RSV Live-Attenuated Vaccine Candidate Lacking G Protein Mucin Domains Is Attenuated, Immunogenic, and Effective in Preventing RSV in BALB/c Mice. (25th October 2022) - Roe, Molly K; Perez, Maria A; Hsiao, Hui-Mien; Lapp, Stacey A; Sun, He-Ying; Jadhao, Samadhan; Young, Audrey R; Batista, Yara S; Reed, Ryan C; Taz, Azmain; Piantadosi, Anne; Chen, Xuemin; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a leading viral respiratory pathogen in infants. The objective of this study was to generate RSV live-attenuated vaccine (LAV) candidates by removing the G-protein mucin domains to attenuate viral replication while retaining immunogenicity through deshielding of surface epitopes. Methods: Two LAV candidates were generated from recombinant RSV A2-line19F by deletion of the G-protein mucin domains (A2-line19F-G155) or deletion of the G-protein mucin and transmembrane domains (A2-line19F-G155S). Vaccine attenuation was measured in BALB/c mouse lungs by fluorescent focus unit (FFU) assays and real-time polymerase chain reaction (RT-PCR). Immunogenicity was determined by measuring serum binding and neutralizing antibodies in mice following prime/boost on days 28 and 59. Efficacy was determined by measuring RSV lung viral loads on day 4 postchallenge. Results: Both LAVs were undetectable in mouse lungs by FFU assay and elicited similar neutralizing antibody titers compared to A2-line19F on days 28 and 59. Following RSV challenge, vaccinated mice showed no detectable RSV in the lungs by FFU assay and a significant reduction in RSV RNA in the lungs by RT-PCR of 560-fold for A2-line19F-G155 and 604-fold for A2-line19F-G155S compared to RSV-challenged, unvaccinated mice. Conclusions: Removal of the G-protein mucin domains produced RSV LAV candidates that were highly attenuated with retained immunogenicity. Abstract : A respiratory syncytial virus (RSV) live-attenuated vaccine (LAV) candidate lacking G protein mucin domains was generated using reverse genetics. The LAV was highly attenuated, but retained immunogenicity and protective efficacy comparable to wild-type infection in a mouse model.